UPAYA HUKUM DALAM PRESPEKTIF HUKUM ISLAM - Rahmiati, Rahmiati (Alhurriyah, 2010)
The basic law of the validation of legal remedy is not specifically finding out in the text of Al-Qurâ€™an and Al-Sunnah, thus such case could be fixed based on the approach method of istinbath â€œmaslahahâ€. This is aimed for realizing the purposes of human beings to protect their rights as the demand of human beings in their life that hopefully it could be an important component to create a justice civilization.